Genetic Identification of Homozygous Familial Hypercholesterolemia by Long-Read Sequencing Among Patients With Clinically Diagnosed Heterozygous Familial Hypercholesterolemia. (24th March 2023) - Chaudhry, Ahsen; Trinder, Mark; Vesely, Kristin; Cermakova, Lubomira; Jackson, Linda; Wang, Jian; Hegele, Robert A.; Brunham, Liam R.
Abstract : Background: Homozygous familial hypercholesterolemia (HoFH) is a rare genetic disorder characterized by extremely elevated plasma low-density lipoprotein cholesterol and accelerated atherosclerosis. Accurate identification of patients with HoFH is essential as they may be eligible for specialized treatments. We hypothesized that a subset of patients with clinically diagnosed heterozygous FH (HeFH) may in fact have HoFH, and this could be identified by genetic diagnosis. Methods: We recruited patients with a clinical diagnosis of HeFH based on a Dutch Lipid Clinic Network score ≥6 and no secondary cause of hypercholesterolemia. We performed targeted next-generation sequencing of the low-density lipoprotein receptor ( LDLR ), apolipoprotein B ( APOB ), proprotein convertase subtilisin/kexin type 9 ( PCSK9 ), and low-density lipoprotein receptor adapter protein 1 ( LDLRAP1 ) genes, followed by long-read sequencing of the LDLR gene in patients with >1 pathogenic LDLR variant. We examined lipid levels and cardiovascular events. Results: Among 705 patients with clinically diagnosed HeFH, we identified a single pathogenic variant in 300 (42.6%) and >1 pathogenic variant in the LDLR gene in 11 patients (1.6%). We established a genetic diagnosis of HoFH in 6 (0.9%) patients (3 true homozygotes and 3 compound heterozygotes). The mean baseline low-density lipoprotein cholesterol and prevalence of premature cardiovascular disease of patients with genetically identified HoFH was significantly higher than patients with HeFH. Conclusions: In a cohort of patients with clinically diagnosed HeFH, genetic testing including long-read sequencing revealed that 0.9% had HoFH. These patients tended to have a more severe clinical phenotype. Genetic testing of patients with clinical FH may identify patients with HoFH that had eluded clinical diagnosis.